Quantitative Analysis of Porcine Endogenous Retroviruses in Different Organs of Transgenic Pigs Generated for Xenotransplantation - Mazurek, Urszula; Kimsa, Magdalena C.; Strzalka-Mrozik, Barbara; Kimsa, Malgorzata W.; Adamska, Jolanta; Lipinski, Daniel; Zeyland, Joanna; Szalata, Marlena; Slomski, Ryszard; Jura, Jacek; Smorag, Zdzislaw; Nowak, Roman; et al. (Current microbiology, 2013)
The pig appears to be the most promising animal donor of organs for use in human recipients. Among several types of pathogens found in pigs, one of the greatest problems is presented by porcine endogenous retroviruses (PERVs). Screening of the source pig herd for PERVs should include analysis of both PERV DNA and RNA. Therefore, the present study focuses on quantitative analysis of PERVs in different organs such as the skin, heart, muscle, and liver and blood of transgenic pigs generated for xenotransplantation. Transgenic pigs were developed to express the human α-galactosidase, the human α-1,2-fucosyltransferase gene, or both genetic modifications of the genome (Lipinski et al., Medycyna Wet 66:316–322, 2010 ; Lipinski et al., Ann Anim Sci 12:349–356, 2012 ; Wieczorek et al., Medycyna Wet 67:462–466, 2011 ). The copy numbers of PERV DNA and RNA were evaluated using real-time Q-PCR and QRT-PCR, respectively. Comparative analysis of all PERV subtypes revealed the following relationships: PERV A > PERV B > PERV C. PERV A and B were found in all samples, whereas PERV C was detected in 47 % of the tested animals. The lowest level of PERV DNA was shown in the muscles for PERV A and B and in blood samples for PERV C. The lowest level of PERV A RNA was found in the skin, whereas those of PERV B and C RNA were found in liver specimens. Quantitative analysis revealed differences in the copy number of PERV subtypes between various organs of transgenic pigs generated for xenotransplantation. Our data support the idea that careful pig selection for organ donation with low PERV copy number may limit the risk of retrovirus transmission to the human recipients.